Innovative HIV/AIDS program launched in Ottawa. - Martin, M (1995)
Collaboration among 31 social and health care agencies and the provincial government has resulted in an innovative program for Ottawa-area patients with HIV infection or AIDS. The target group is the homeless and people with "unstable" housing who live in the city's downtown core, a group at high risk of contracting HIV. The education of family practitioners will be an important part of the program.